The Effect of Relationship Marketing on Customer Gratitude and Customer Loyalty at Farm to Table Business - Mekasari, Firsta Koesdyah; Setiawan, Budi; Isaskar, Riyanti; Koestiono, Djoko; Syafrial; Maulidah, Silvana (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2023)
Farm to Table Business is one of the platform for selling agricultural products by digital marketing that really needs a relationship marketing strategy to add customers and increase customer loyalty by increasing customer gratitude. Relationship marketing is a form of strategy to retain customers. The purpose of this research is to analyze the effect of relationship marketing on customer gratitude and the effect of customer gratitude on customer loyalty at Farm to Table Business. This study used a purposive sampling technique to determine the sample with a total of 100 respondents. The data analysis technique in this study used SEM PLS (Partial Least Square) with Warp PLS 7.0 software. The results of this research show that: (1) Relationship marketing has a positive and highly significant effect on customer gratitude by 0.22; (2) Customer Gratitude has a positive and highly significant effect on customer loyalty by 0.56.